Economics of Horizontal Integration in Poultry Industry in South-West Nigeria - Moses , Bamiro, Olasunkanmi; Olanrewaju, Otunaiya, Abiodun; Olubanjo, Idowu, Adewunmi (International Journal of Poultry Science, 2011)
The broad objective of this study is to analyze the economics of horizontal integration in poultry production in some selected local government areas in south-west, Nigeria. Data was collected from 61 fish farmers, 40 poultry farmers and 53 integrated fish and poultry farms, making a sample size of 154 farmers using purposive-snowball sampling process. Descriptive statistics, gross margin analysis and stochastic cost frontier were employed for data analysis. Analysis of socio-economic characteristics shows that most of the farmers in the study area are males, young within the age range of 30-<60 years and had formal education. Most of the farms are solely owned and some of the farmers are part-time farmers. Analysis of cost shows that feed account for 55.8, 68.2 and 78.9% of variable cost of production for sole fish farming, integrated poultry and fishery as well as sole poultry farming respectively. Followed closely in the same order is the cost of labour which account for 26, 6.4 and 3.7% cost of production respectively. The gross margin analysis shows that horizontally integrated poultry farms have highest gross margin ( 1,994,792.88) while the sole fish enterprise records the least gross margin of 556,516.32. This confirms the economic importance of horizontal integration in poultry industry in terms of profitability. The price of eggs, flock size, stocked fingerlings, quantity of feed and cost of intermediate materials are the explanatory variables that influence the production cost while age of the farmers, vertical integration and sole fish farming are the determinants of economic efficiency.